1996
DOI: 10.1093/carcin/17.11.2469
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the mutagenic/carcinogenic imidazoquinoxaline-type heterocyclic amines through the unstable free radical Maillard intermediates and its inhibition by phenolic antioxidants

Abstract: Generation of the imidazoquinoxaline-type heterocyclic amines in the heated model system composed of glucose/glycine/creatinine in aqueous diethylene glycol was effectively prevented by phenolic antioxidants, butylated hydroxyanisole (BHA), propyl gallate (PG), sesamol, esculetin and epigallocatechin gallate (EGCG) in a dose-dependent manner. Generation of the mutagens in heated-and-dried bonito meat was effectively prevented on pretreatment with EGCG or green tea extract. Electron spin resonance (ESR) studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 28 publications
2
53
0
3
Order By: Relevance
“…Imidazoquinoxaline type HCAs are formed in the model mixture consist of glucose, glycine and creatinine through free radical Maillard intermediates, a pyrazine cation radical and carbon-centered radicals [31][32][33][34]. In the initial stage of Maillard reaction of glucose with glycine, both pyrazine cation radical and cation centered radicals are generated and in the presence of phenolic antioxidants they are scavenged [31].…”
Section: Precursors and Factors Of Hcas Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Imidazoquinoxaline type HCAs are formed in the model mixture consist of glucose, glycine and creatinine through free radical Maillard intermediates, a pyrazine cation radical and carbon-centered radicals [31][32][33][34]. In the initial stage of Maillard reaction of glucose with glycine, both pyrazine cation radical and cation centered radicals are generated and in the presence of phenolic antioxidants they are scavenged [31].…”
Section: Precursors and Factors Of Hcas Formationmentioning
confidence: 99%
“…In the initial stage of Maillard reaction of glucose with glycine, both pyrazine cation radical and cation centered radicals are generated and in the presence of phenolic antioxidants they are scavenged [31]. In the model mixture composed of glucose, glycine and creatinine has shown that epigallocatechin gallate and flavonoids prevent the HCAs formation [35].…”
Section: Precursors and Factors Of Hcas Formationmentioning
confidence: 99%
“…O ile w układzie modelowym, zastosowanym przez Kato i wsp. [27], zaobserwowano zmniejszenie stężenia amin z grupy imidazochinoksalin pod wpływem BHA i PG, to Johansson i wsp. [26] …”
Section: Występowanie I Powstawanie Hca W Produktach Mięsnychunclassified
“…One such strategy could be mixing of ground meat with water binding compounds such as soy protein, starch, or other polysaccharides, which help lower surface temperature and hinder transport of water soluble precursors [55,223,224]. Moreover, this practice minimizes water loss during cooking and the resulting high water content may also suppress formation of intermediary pyrazine cation radicals [223,225].…”
Section: Temperature Time and Water Contentmentioning
confidence: 99%
“…Various synthetic and natural agents have been reported to have modulating effects on the formation of HAs [29,235]. The importance of the former has been demonstrated through identification of inhibitors of this type [18,225]; nevertheless, the ultimate goal should be directed at identification of inhibitors from plants, preferably dietary plants or their products. As antioxidative activity has been the most popular mechanism of inhibition proposed, phenolic compounds occupy the largest proportion of putative phytochemicals investigated [27,29,58].…”
Section: Presence/addition Of Inhibitorsmentioning
confidence: 99%